Echocardiographic abnormalities in primary antibody deficiency. Issue 942 (13th April 2004) - Johnston, S L; Hill, S J; Lock, R J; Dwight, J F; Unsworth, D J; Gompels, M M
Abstract : Objective: To document cardiac abnormalities secondary to pulmonary disease in primary antibody deficiency. Patients and methods: A cross sectional audit study of patients from a regional immunology centre. Subjects undergoing two dimensional and Doppler transthoracic echocardiography were reviewed. Ventricular dimensions and function, valvular competence, and estimated pulmonary artery pressure were recorded. Data were compared with clinical variables, pulmonary function tests, and thoracic computed tomography data. Results: Nineteen patients with common variable immunodeficiency and one with IgG2 subclass deficiency were included, mean age at diagnosis 37.5 years, mean estimated diagnostic delay 10.94 years. Left ventricular impairment was found in 15% and right heart dilatation in 20%. Pulmonary hypertension (mean pulmonary artery pressure >25 mm Hg) was found in 45% (9/20), graded as moderate (40–60 mm Hg) in 44% of cases. Pulmonary function was obstructive in 47% (9/19). Fifty five percent of the patients with computed tomography data within the last five years (10/18) had confirmed bronchiectasis. Patients with right heart dilatation and/or moderate pulmonary hypertension (n = 6) had a more prolonged diagnostic delay (p = 0.04) and more severe lung disease. Conclusion: Echocardiographic abnormalities are common in primary antibody deficiency, associated with diagnostic delay and pulmonary complications. Pulmonary hypertension should be considered in those with severe lung disease and can be confirmed by echocardiography.